Pengembangan Lembar Kerja Peserta Didik Berkarakter Islami pada Praktikum Pembelajaran IPA di MTS Raudhatul Akmal - Raudhatul Jannah; Salsa Dianty Yolanda; Syarifah Widya Ulfa (Departement of Mathematics Education, 2023)
The laboratory has a very important role in learning science education, and science educators are advised to apply practicum activities in the learning process because there are many benefits that students can get in doing practicum. The problem-based student worksheet (LKPD) used in this study is a problem-based student worksheet. Student worksheets are expected to be able to develop knowledge through problems given by the existence of problems students are required to solve problems in accordance with the knowledge possessed by students. Efforts that can be made in overcoming problems in learning are by holding practicums in the classroom. The purpose of this research is to develop student worksheets with Islamic character in science learning practicum at MTS Raudhatul Akmal. This research method uses survey methods and literature review. This research method uses Development carried out by research and development methods (Research and Development). The development model in this study is the Borg and Gall model. The research subjects were students of class VII and class VIII MTS Raudhatul Akmal Batang Kuis because they had knowledge and understanding of Islamic religious values. Research data were collected using expert validation sheets, teacher response sheets, student response sheets and data analysis using a Likert scale.